Pengembangan Model Pembelajaran SVRK (Self-Video Recording and Kinesthetic) Pada Mata Kuliah Bahasa Inggris Berbasis Potensi Pertanian Lokal - Imam Suhaimi; Indana Mardatilla (Aksara: Jurnal Bahasa dan Sastra, 2018)
The SVRK (Self-Video Recording and Kinetic) learning model is a language learning model developed to achieve Self Regulated Learning of agricultural students in English based on local agricultural potential. The purpose of this study is (1) to produce and describe, (2) to describe feasibility, and (3) to describe the model of product use in learning English. This research is a development research that refers to the Research and Development (R D) development model of Borg and Gall. The steps of research include: (1) analyzing potential and problems, (2) designing products, (3) collecting material, (4) making initial products, (5) conducting expert tests, (6) revising products, and (7) conduct field tests. The results of this research indicate that students are able to improve their English language skills by using local agricultural potential, and conduct self-evaluation well.Keywords: SVRK Learning Model, Self-Regulated Learning, local agricultural potential DOI: http://dx.doi.org/10.23960/aksara/v19i2.pp68-88